Enhancing Classroom Management Through Digital Tools: A Study on Lecturer Readiness and Implementation - Cut Mawar Helmanda; Rahmatun Nisa (Advances In Education Journal, 2026)
This study investigates the challenges lecturers face in managing classrooms in the digital era and examines how digital tools can enhance classroom management in English language classes at Universitas Muhammadiyah Aceh. The research aimed to explore lecturer readiness and the effectiveness of digital tools in supporting instructional organization and student behavior management. Using a qualitative design, data were collected through classroom observations and semi-structured interviews with three English lecturers. Findings show that digital tools improved instructional flow, facilitated student engagement, and supported the monitoring of learning activities. The study concludes that English lecturers at Universitas Muhammadiyah Aceh demonstrate strong readiness in integrating digital tools, enabling effective classroom management and organized, interactive learning environments. The findings highlight that sustained institutional support and ongoing professional development will further strengthen these successful technology-enhanced practices